2016
DOI: 10.1073/pnas.1618773114
|View full text |Cite
|
Sign up to set email alerts
|

TIFA as a crucial mediator for NLRP3 inflammasome

Abstract: Toll-like receptor-mediated NF-κB activation is a major innate immune reaction of vascular endothelial cells (ECs) in response to prooxidative and proinflammatory stimuli. We identified that TNF-α receptor-associated factor-interacting protein with a forkhead-associated domain (TIFA) is a regulator of priming (signal 1) and activating (signal 2) signals of nucleotide oligomerization domain-like receptor family pyrin domain-containing protein 3 (NLRP3) inflammasome in ECs. Oxidative and inflammatory stresses su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 46 publications
(62 reference statements)
3
44
0
Order By: Relevance
“…This observation was consistent with the binding preference of the FHA domain for phosphorylated threonine over phosphorylated serine (11,12,28). Indeed, we found threonine 9 of TIFA was phosphorylated in response to DNA insults, and the FHA-pThr interaction was crucial for TIFA-mediated NF-B activation in genotoxic conditions as its roles in other inflammatory pathways (14,23,29). Benefits of chromatin enrichment of TIFA for NF-B activation could be easily grasped with the fact that oligomerization is a prevailing mechanism for ubiquitination-based efficient assembly of IKK complex (4,5).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This observation was consistent with the binding preference of the FHA domain for phosphorylated threonine over phosphorylated serine (11,12,28). Indeed, we found threonine 9 of TIFA was phosphorylated in response to DNA insults, and the FHA-pThr interaction was crucial for TIFA-mediated NF-B activation in genotoxic conditions as its roles in other inflammatory pathways (14,23,29). Benefits of chromatin enrichment of TIFA for NF-B activation could be easily grasped with the fact that oligomerization is a prevailing mechanism for ubiquitination-based efficient assembly of IKK complex (4,5).…”
Section: Discussionsupporting
confidence: 88%
“…Another interesting finding from this study was the common Thr-9 phosphorylation events for both canonical inflammation and DNA damage-signaling pathways, despite that different kinases might be involved (29,33). Although the whole picture for the differences of these cascades was currently unknown, nucleus translocation and chromatin enrichment of TIFA could only be observed in DNA-damaged conditions, but not in inflammatory cascades, suggested that additional regulations exist to account for DNA damageinduced subcellular translocation.…”
Section: Discussionmentioning
confidence: 68%
“…Stimulation of NF-κB activation by common inducers, such as IL-1β or TNF-α, involves canonical pathways, whereas stimulation by ADP heptose and HBP leads to the formation of the large TIFAsome complex, which, as we revealed previously (9), associates multiple signaling molecules that may have a capacity to stimulate additional routes, such as MAPK pathways. Likewise, a recent report showed that signaling via TIFA can lead to activation of the inflammasome (28). It will certainly be interesting to explore the spectrum of ALPK1-TIFA–dependent pathways in greater depth.…”
Section: Discussionmentioning
confidence: 99%
“…24 It was first described that TIFA plays a crucial role in NLRP3 inflammasome priming and activation. 25 In this study, arteries and cultured endothelial cells exposed to mechanical stress and oxidized low-density lipoprotein have increased the activation of sterol regulatory elementbinding protein 2 (SREBP2) to enhance the transcription of TIFA and NLRP3. In addition, SREBP2-mediated overexpression of TIFA caused NF-kB activation, which was also contributing to the overexpression of NLRP3 and inflammasome components, such as the inactive proforms of caspase-1 and IL-1b, respectively.…”
Section: Tifa and Alpk1 As Crucial Mediators Of Nf-kb Activationmentioning
confidence: 98%